A prodrug of 3-(ferrocenylaminocarbonyloxymethyl)phenol activated by reactive oxygen species in cancer cells - Özkan, Hülya Gizem; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2022)
Hybrid drugs containing ferrocene and phenol residues, whose π systems are not conjugated with each other, exhibit potent anticancer activity as previously reported. Few important open questions are remaining before practical application of these drugs becomes possible. First, their mode of action is not fully clarified. Second, it is not known whether these drugs exhibit cancer cell specificity. Third, due to the presence of the phenol moiety, these drugs can potentially be oxidatively deactivated and eliminated via phase II metabolism when applied in vivo. In this paper we report on synthesis of three prodrugs of aminoferrocene-phenol hybrids, where the phenolic OH group is masked as a boronic acid pinacol ester. We confirmed that the best prodrug in this small series p5 is activated in human ovarian cancer A2780 and Burkitt's lypmphoma BL-2 cells, but remains inactive in representative normal SBLF9 cells. Since p5 does not contain free phenolic OH groups, it will not be metabolized as phenols in vivo. We confirmed that the mechanism of anticancer activity of aminoferrocene-phenol prodrug p5 relies on generation of reactive oxygen species in cells.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Aminoferrocene; Anticancer; Mitochondria; Phenol; Prodrug; Reactive oxygen species